La patria potestad de los hijos en los procesos de divorcio y la modificación al artículo 110 numeral 1 del Código Civil Ecuatoriano - González Herrera, Diego Guillermo (2016)
Within this research we have taken this problematization which is undoubtedly an issue that currently is taken often as it is the dispute of the children in divorce proceedings since at present family stability has been staggering in many homes for different reasons and motives and now is very normal to see mothers suing their parents for food and even refers to a way of life claim food. Our Constitution guarantees the rights of children and adolescents. Putting these rights on the other people. Since this part in which my work analyzes this social problem since even though the marital relationship is not good and should be terminated should not be provided with the relationship father and son or vice versa provided that Can prove that the relationship that this carries with her children is very good and does not affect at all the best interests of the child should be an opportunity so that it can apply for the parental affection of both parents is vital, but it is not fair that one single charge to responsibility and even see it as u ATM which are on call whenever you need money. From another point, he also saw that the laws in these cases are very inclined towards women that not in all cases come to future relationship that can forge between father and son rather look to his former partner as something to destroy, stripped of everything even affect their dignity and worst put against their own children, for the simple reason that their coexistence was not good and was terminated the contract of marriage.